Application of Augmented Reality in the Drawing Engineering Learning Module 2 and CAD in the Building Engineering Education Study Program, Faculty of Engineering, State University of Jakarta - Kaka Sumarna (Jurnal Pensil : Pendidikan Teknik Sipil, 2019)
The purpose of this study is to apply Augmented Reality to the Drawing Engineering Learning Module 2 and CAD. This research is included in Research and Development (R&D) with the Thiagarajan development research model. The steps of research and development are abbreviated as 4D, namely Define, Design, Development and Dissemination. This research used instrument data collection technique, namely questionnaire. The questionnaire was given to material experts and media experts to test the feasibility of instructional media products. The results of the feasibility of learning media products in the form of learning modules and Augmented Reality applications, named ARCAD3D, are as follows: a) the material assessment by the material experts received a value of 81.8182% with a very good interpretation; b) media assessment by media experts gets a value of 85.6% with very good interpretation. Based on the results of the feasibility, it can be concluded that Augmented Reality is very feasible to be applied in the Drawing Technique 2 and CAD learning modules that can help students improve their imagination to draw techniques and can be used by lecturers and students in learning.